Gelation and biocompatibility of injectable alginate–calcium phosphate gels for bone regeneration. Issue 3 (12th June 2013) - Alves Cardoso, D.; van den Beucken, J. J. J. P.; Both, L. L. H.; Bender, J.; Jansen, J. A.; Leeuwenburgh, S. C. G.
Abstract An emerging approach toward development of injectable, self‐setting, and fully biodegradable bone substitutes involves the combination of injectable hydrogel matrices with a dispersed phase consisting of nanosized calcium phosphate particles. Here, novel injectable composites for bone regeneration have been developed based on the combination of ultrapure alginate as the matrix phase, crystalline CaP [monetite and poorly crystalline hydroxyapatite (HA)] powders as both a dispersed mineral phase and a source of calcium for cross‐linking alginate, glucono‐delta‐lactone (GDL) as acidifier and glycerol as both plasticizer and temporary sequestrant. The composites were maximized with respect to CaP content to obtain the highest amount of osteoconductive filler. The viscoelastic and physicochemical properties of the precursor compounds and composites were analyzed using rheometry, elemental analysis (for calcium release and uptake), acidity [by measuring pH in simulated body fluid (SBF)], general biocompatibility (subcutaneous implantation in rabbits), and osteocompatibility (implantation in femoral condyle bone defect of rabbits). The gelation of the resulting composites could be controlled from seconds to tens of minutes by varying the solubility of the CaP phase (HA vs. monetite) or amount of GDL. All composites mineralized extensively in SBF for up to 11 days. In vivo, the composites also disintegrated upon implantation in subcutaneous or bone tissue, leaving behind less degradable but osteoconductive CaP particles. Although the composites need to be optimized with respect to the available amount of calcium for cross‐linking of alginate, the beneficial bone response as observed in the in vivo studies render these gels promising for minimally invasive applications as bone‐filling material. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 808–817, 2014.